(untitled) (Indian Journal of Public Health Research & Development, 2020)
Context: Diabetes mellitus (DM) is a lifelong metabolic disease, considered often as an epidemic problem that leads to a reduction in quality and expectancy of life. There is an increasing prevalence of DM throughout the world as a result of changing dietary patterns and decreased physical activity. The aim of this study is to identify some of the factors that affect the incidence of diabetes at the employees ‘ segment in Basra city. A cross-sectional study was conducted among 120 patients with type 2 diabetes that included 85 male and 35 females. The results have reflected the apparent effect of age, obesity, Genetic history on diabetes, thus Confirmed by the statistical side of the medical opinion and No effect of smoking on diabetes .The results showed the apparent effect factor for age, genetic history and obesity on diabetes while the results confirmed the lack of influence of sex and smoking on diabetes.